Development and initial validation of the implicit internalized sexual orientation stigma affect misattribution procedure - Hall, William J.; Dawes, Hayden C.; Hannay, Jason W.; Williams, Denise Yookong; Frey, Joseph J.; Srivastava, Ankur; Chapman, Mimi V.; Chen, Ding-Geng; Wilson, Amy Blank; Ramon, Magdelene E.; Payne, B. Keith (Frontiers in Psychology, 2024)
Introduction This article describes the development and initial validation of a measure of implicit internalized stigma among queer people, the Implicit Internalized Sexual Orientation Stigma Affect Misattribution Procedure (Internal-SOS-AMP), a computer-administered sequential priming procedure. Methods The creation of the Internal-SOS-AMP involved a mixed-methods approach, including a literature review, expert interviews, stimuli selection and pilot testing, data collection from a large sample, reliability testing, correlational analyses, and confirmatory factor analysis. Psychometric testing was conducted with a national sample of 500 queer adults who completed two waves of data collection. Confirmatory factor analysis was used to evaluate two models: a one-factor model with internalized stigma specified as one overall construct and a two-factor model with internalized stigma specified as two constructs based on binary conceptions of gender (stigma regarding queer women and stigma regarding queer men). Results Results showed that the two-factor model best fit the data. This indicates that although implicit attitudes toward queer men and women are highly correlated, implicit internalized stigma differentiated by two gender stimuli groups (men and women) more accurately reflects the data. There was evidence of convergent validity as Internal-SOS-AMP scores showed small positive associations with explicit internalized stigma. Regarding divergent validity, Internal-SOS-AMP scores were inversely related to affirmation of a queer identity. Reliability results for the Internal-SOS-AMP showed good internal consistency and acceptable test–retest reliability. Discussion The creation of the Internal-SOS-AMP used best practices for measurement development. Psychometric findings show strong evidence of content validity, convergent validity, divergent validity, and reliability of the Internal-SOS-AMP.